The determination of the hepatoprotective activity of corn (Zea mays L.) cob extract in male Sprague Dawley rats - Baquiran, Lorenzo Carlos​; Hao, Kenard C.​; Ong, Dyan Cathrine S.​
Introduction: Liver disease affects millions of Filipinos which may increase due to Westernized lifestyle practices. Due to this, silymarin is consumed for their hepatoprotective properties, however, at a great cost since silymarin is not endemic to the country. Corn (Zea mays L.) has been found to have potential antioxidant activity which can also exhibit hepatoprotective activity.